Broadband tunable polarization rotator based on the waveguiding effect of liquid crystals. (22nd June 2021) - Choi, Yeongyu; Oh, Seung-Won; Sohn, Ho-Jin; Yoon, Tae-Hoon
Abstract: A tunable liquid crystal (LC) polarization rotator that can rotate the polarization axis of linearly-polarized broadband light is achieved by using an asymmetrically-anchored negative LC cell. Interdigitated electrodes are used to apply an in-plane field to control the twist angle. The use of the asymmetrical anchoring in the LC cell enables continuous change of the twist angle by increasing the applied electric field. For uniform transmission, we used an LC that has negative dielectric anisotropy to avoid tilting of LC molecules by the vertical component of the electric field. We theoretically and experimentally confirmed that the fabricated LC cell could continuously change the twist angle and rotate the polarization axis of the linearly-polarized broadband incident light.